2015
DOI: 10.1016/j.ijhydene.2015.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of applying high strength steels in hydrogen gas pipelines

Abstract: Available online xxx Keywords:Steel Hydrogen Pipeline Fatigue Welding Cost a b s t r a c t Steel pipelines will likely be employed extensively to transport gaseous hydrogen in support of a future clean energy economy. To date, a hydrogen-specific cost analysis of pipeline installation has not been produced. This paper performs several cost analyses in order to quantify cost differentials associated with hydrogen pipeline installation relative to (a) natural gas pipeline installation, (b) use of different pipe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 8 publications
0
28
0
2
Order By: Relevance
“…Therefore, higher-strength pipeline steels, such as X70, can be used with the same safety and reliability as X52 for hydrogen transport applications, which will allow for cost savings. The cost savings can be realized because the difference between X52 and X70 steels comes predominantly from processing, rather than chemistry, and the increased strength of X70 yields thinner pipe wall thicknesses and less tonnage of steel [15][16][17]37].…”
Section: Fatigue Tests In Hydrogen Gasmentioning
confidence: 99%
“…Therefore, higher-strength pipeline steels, such as X70, can be used with the same safety and reliability as X52 for hydrogen transport applications, which will allow for cost savings. The cost savings can be realized because the difference between X52 and X70 steels comes predominantly from processing, rather than chemistry, and the increased strength of X70 yields thinner pipe wall thicknesses and less tonnage of steel [15][16][17]37].…”
Section: Fatigue Tests In Hydrogen Gasmentioning
confidence: 99%
“…The change in thermodynamic conditions with an increased hydrogen content may also affect the natural gas transmission system (i.e., gas compression stations or gas reduction stations). Another important issue is selection of the material for pipeline construction in light of the hydrogen corrosion case [42], which affects the cost of its construction [20,43].…”
Section: Methane-hydrogen Mixturesmentioning
confidence: 99%
“…The recent HA-FCG results produced by the two laboratories indicate that the design penalty placed upon higher strength steels is overly conservative and without justification. Studies have shown that allowing pipeline steels with a SMYS of up to 480 MPa (70 ksi) without penalty could reduce material and installation costs by approximately 25% [11]. As a result, the forthcoming version of the ASME B31.12 code will remove the design penalties on materials with a SMYS between 360 MPa and 480 MPa (52 ksi and 70 ksi).…”
Section: Introductionmentioning
confidence: 99%